Male poplars have a stronger ability to balance growth and carbohydrate accumulation than do females in response to a short‐term potassium deficiency. Issue 4 (18th February 2015) - Yang, Yanni; Jiang, Hao; Wang, Maolin; Korpelainen, Helena; Li, Chunyang
Abstract : Potassium (K) deficiency influences plant performance, such as ion uptake and carbohydrate transport. However, little is known about differences between males and females in response to K deficiency. In this study, dry matter accumulation, photosynthetic capacity, allocation patterns of K +, Na + and carbohydrates, and ultrastructural changes in males and females of Populus cathayana exposed to K deficiency were investigated. The results indicated that males maintained a significantly higher K + content and K + /Na + ratio in leaves and stems than did females under K deficiency. Moreover, K deficiency significantly increased the sucrose content of females, whereas no significant effect on males was detected. In addition, a comparative analysis showed that males allocated more resources to roots, while females allocated more to leaves, which resulted in sexually different root/shoot (R/S) ratios. Transmission electron microscopic (TEM) observations showed that males suffered fewer injuries than did females. These results suggested that males have a better ability to cope with K deficiency. In addition, the combined effects of salinity and K deficiency on poplars were studied. The results indicated that salt stress aggravates the negative effects caused by K deficiency. Taken together, our study provided evidence for gender‐specific strategies in ion and carbohydrate allocation in poplars exposed to a short‐term K deficiency. In leaves and stems, the lower K + accumulation inhibited sucrose translocation and resulted in a decreased R/S ratio, which may contribute to males having a stronger ability to balance growth and carbohydrate accumulation when compared with females.